2007
DOI: 10.1037/0012-1649.43.6.1531
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in resistance to peer influence.

Abstract: Prior research describes the development of susceptibility to peer pressure in adolescence as following an inverted U-shaped curve, increasing during early adolescence, peaking around age 14, and declining thereafter. This pattern, however, is derived mainly from studies that specifically examined peer pressure to engage in antisocial behavior. In the present study, age differences and developmental change in resistance to peer influence were assessed using a new self-report instrument that separates susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
1,087
15
29

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,242 publications
(1,192 citation statements)
references
References 42 publications
61
1,087
15
29
Order By: Relevance
“…As a result, we cannot draw conclusions from the current study about whether the results are unique to prosocial behaviour (although studies indicate that age‐related decreases in social influence are seen for other types of behaviour too, such as risk perception and antisocial behaviour; Knoll et al., 2015, 2017; Steinberg & Monahan, 2007; Sumter et al., 2009). Further studies could assess how age affects prosocial, neutral and antisocial influence within the same paradigm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, we cannot draw conclusions from the current study about whether the results are unique to prosocial behaviour (although studies indicate that age‐related decreases in social influence are seen for other types of behaviour too, such as risk perception and antisocial behaviour; Knoll et al., 2015, 2017; Steinberg & Monahan, 2007; Sumter et al., 2009). Further studies could assess how age affects prosocial, neutral and antisocial influence within the same paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that susceptibility to social influence is at its highest in late childhood (approximately age 8–10 years) then gradually decreases across the adolescent years (approximately 11–18 years) and into adulthood (19 years and above; Knoll, Leung, Foulkes, & Blakemore, 2017; Knoll, Magis‐Weinberg, Speekenbrink, & Blakemore, 2015; Steinberg & Monahan, 2007; Sumter, Bokhorst, Steinberg, & Westenberg, 2009). As such, relative to adults, children and adolescents are particularly susceptible to being influenced by others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Il y a quand même fort à parier que l'argent qu'il en tirerait lui servirait au moins en partie à consommer. En ce sens, l'adolescence est une période où il est très important de plaire aux pairs, ce qui peut même constituer une motivation à s'engager dans la délinquance (Brown et Larson, 2009 ;Brunelle et al, 2005 ;Monahan, Rhew, Hawkins et Brown, 2013 ;Steinberg et Monahan, 2007). De plus, l'explication économico-compulsive postule que la consommation de SPA précède la commission de délits lucratifs.…”
Section: Limitesunclassified
“…dolescents differ in their sensitivity to peer pressure, and their ability to resist peer influences; the latter trait can be assessed with a self-report questionnaire designed to minimize socially desirable responding (Steinberg and Monahan 2007). Which neural systems -if any -are engaged differentially in children or adolescents who differ in their resistance to peer influences?…”
mentioning
confidence: 99%